PENGARUH FLY ASH TERHADAP KADAR SO3 DAN WAKTU IKAT SEMEN - Rahayu, Putri; Mariyamah, Mariyamah; Anase, Novadri; Safaruddin, Safaruddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Cement is the main material in construction which is produced from various raw materials such as limestone, iron sand, clay, silica sand, and gypsum. One of the additives often used in cement production is fly ash, which is the residue of burning coal which has the main content of SiO?, Al?O?, and Fe?O?. This study aims to review the effect of using several fly ash on SO? content and cement binding time, in order to optimise the use of fly ash as an environmentally friendly additive while improving cement quality. The results of the analysis The use of different fly ash with a percentage of 10% and 15% of the lowest SO3 content is PLTU bukit asam and the highest is PT Priamanaya The use of fly ash with a percentage of 10% and 15% of different types also affects the binding time. The difference in binding time in different types of fly ash is caused by several factors, namely the particle size of fly ash also affects the binding time. Fly ash with larger or coarser particles tends to slow down the binding time. and Different Chemical composition Fly ash consists of oxides such as silica (SiO?), alumina (Al?O?), calcium (CaO), and iron (Fe?O?). The longest binding time of acid hill power plant and the fastest binding time of PT Priamanaya